Propuesta para la implementación del presupuesto integral como instrumento de control financiero en la Compañía Abc C. Ltda. 2019. - Tituana Aguilar, Jimmy Oscar (My University, 2019)
The present work of complex examination is aimed at companies of all kinds, especially SMEs, to analyze the importance of carrying out an integral budget and the achievement of results, with this the emergence of the comprehensive budget has the purpose of controlling the activities that exercises an entity and project itself through time according to the desired future, in order to determine the means necessary to achieve them. For this the Company ABC C.Ltda. that elaborates and distributes a popular consumer product marketed in several cities, maintains as a means of planning and control conventional states for decision making, and that according to the sales forecasts determines, warns of the need to implement a general system that contains all the budgets according to the area. For this we will ask the conventional states that the company manages and adjust them to the integral budget to adhere to a truthful, timely and adequate information, the integral budget or also called teacher manages to establish guidelines that facilitate an entity to observe where the company is headed and the changes that must be executed according to their convenience these are events that occur in the future and who anticipates them in a timely manner will have a competitive advantage because it clarifies when buying more, for later sale and when leveraging as the case or not running out of liquidity, it is an evil that afflicts many entities that do not plan their activities, hence the importance of having such a comprehensive budget for any organization.
El presente trabajo de examen complexivo está dirigido a las empresas de toda índole en especial las PYMES, para que analicen la importancia que conlleva realizar un presupuesto integral y la consecución de resultados, con esto el surgimiento del presupuesto integral tiene la finalidad de controlas las actividades que ejerce una entidad y proyectarse a través del tiempo según el futuro deseado, con el fin de determinar los medios necesarios para lograrlos. Para esto la Compañía ABC Cia. Ltda. que elabora y distribuye un producto de consumo popular comercializada en varias ciudades, mantiene como medio de planificación y control estados convencionales para la toma de decisiones, y que según los pronósticos de venta determina, advierte la necesidad de implementar un sistema general que contenga todos los presupuestos según el área. Para esto se pedirá los estados convencionales que la empresa maneje y ajustarlos al presupuesto integral para apegarnos a una información veraz, oportuna y adecuada, el presupuesto integral o llamado también maestro logra establecer lineamientos que facilitan a una entidad observar hacia donde se dirige la empresa y los cambios que debe ejecutar según su conveniencia estos son sucesos que ocurren a futuro y quien los anticipe de manera oportuna tendrá una ventaja competitiva pues esclarece cuando comprar más, para posterior venta y cuando apalancarse según sea el caso o no quedarse sin liquidez, pues es un mal que aqueja a muchas entidades que no planifican sus actividades, de aquí la importancia de contar con dicho presupuesto integral para cualquier organización.
Keywords: PLANIFICACIÓN; CONTROL; PRESUPUESTO; PROCESO; INFORMACIÓN